2022
DOI: 10.3389/fonc.2022.980765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real-world data (RWD) analysis on efficacy and post-progression outcomes with pembrolizumab plus chemo vs chemo alone in metastatic non-squamous non-small cell lung cancer with PD-L1 < 50%

Abstract: BackgroundFollowing the introduction of immunotherapy (IO) in the first-line (1L) treatment in patients with non-small cell lung cancer (NSCLC) without sensitizing EGFR/ALK mutations, increasing real-world data depict how difficult it is to replicate data from clinical trials to clinical practice, with high rates of early treatment failure. In the context of chemo-IO, our study aims to compare platinum-pemetrexed-pembrolizumab combination to platinum-doublet alone in patients with low PD-L1 (&lt;50%).Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In our analysis, age was not significant, while performance status, higher disease burden, and disease progression had a negative impact on OS. Other authors have confirmed those observations and highlighted the impact of performance status and a higher probability of premature termination of treatment in real life than in clinical trials (24)(25)(26)(27). Table 5 includes a summary of real-world studies in NSCLC patients with tumours showing negative PD-L1 expression.…”
Section: Discussionmentioning
confidence: 75%
“…In our analysis, age was not significant, while performance status, higher disease burden, and disease progression had a negative impact on OS. Other authors have confirmed those observations and highlighted the impact of performance status and a higher probability of premature termination of treatment in real life than in clinical trials (24)(25)(26)(27). Table 5 includes a summary of real-world studies in NSCLC patients with tumours showing negative PD-L1 expression.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, patients with a relatively favorable prognosis may have been included in the SEQ group compared to those in the CIT group. In previous reports, approximately 8% of the patients failed to switch to second-line treatment after first-line treatment, suggesting that the SEQ strategy for these patients would jeopardize the opportunity for ICI treatment [26]. Third, the difference in the follow-up period and subsequent treatment options may have affected the outcomes since CIT was approved approximately two years later than second-line ICI monotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Although several reports have compared the prognostic value of CIT and pembrolizumab monotherapy [22][23][24][25], reports comparing CIT and SEQ are scarce, with only one report on non-squamous NSCLC with a small sample size showing the non-inferiority of sequential treatment over CIT [26]. Thus, whether SEQ in patients with NSCLC with ≤49% PD-L1 expression is comparable to that of CIT is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Observational data from clinical practice for pembrolizumab plus chemotherapy for older adult patients in China indicated that grade 3 and higher pneumonitis occurred in 9%, and AEs leading to discontinuation registered 26% . Another study conducted in Italy reported grade 3 and higher pneumonitis occurring in 10.2% of patients receiving a combination of pembrolizumab, platinum, and pemetrexed with a median age of 68 years . Furthermore, Morimoto et al reported that the incidence of grade 3 and higher pneumonitis reached 16.0% in patients 75 years and older who received pembrolizumab with platinum and pemetrexed in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another study conducted in Italy reported grade 3 and higher pneumonitis occurring in 10.2% of patients receiving a combination of pembrolizumab, platinum, and pemetrexed with a median age of 68 years. 31 Furthermore, Morimoto et al 32 reported that the incidence of grade 3 and higher pneumonitis reached 16.0% in patients 75 years and older who received pembrolizumab with platinum and pemetrexed in Japan. Considering these results, ICI-chemotherapy resulted in an increased frequency of severe pneumonitis relative to ICI alone, especially in older adults.…”
Section: Discussionmentioning
confidence: 99%